Pengaruh Lama Fermentasi menggunakan Isolat Lactobacillus rhamnosus MY2 terhadap Karakteristik Susu Kacang Tanah (Arachis hypogaea L.) - Aulia, Erza; Sugitha, I Made; Selamet Duniaji, Agus (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p04, 2023)
This research aims to identify the effect of fermentation time with Lactobacillus rhamnosus MY2 isolate on the characteristics of peanut milk and determine the right fermentation time to produce fermented peanut milk with the best characteristics. This research used a completely randomized design (CRD) with variations in fermentation time which consisted of 3, 6, 9, 12, and 15 hours. The treatment was repeated 3 times to produce 15 experimental units. The data obtained were analyzed using the analysis of variance (ANOVA) method and if the treatment had a significant effect (P<0.05) on the observed variables, then continued with Duncan New Multiple Range Test (DNMRT). The results showed that the treatment of fermentation time had a significant effect on the pH, total LAB, total acid, the value of preference for aroma and taste, the value of score for sour taste and viscosity, and overall acceptance but had no significant effect on protein content, fat content, the value of preference for color and texture of fermented peanut milk. The 6 hours fermentation time produce the best characteristics of fermented peanut milk with criteria pH 5.43, total LAB 8.52 Log CFU/ml, total acid 0.13%, protein content 3.27%, fat content 22.78%, the color, aroma, sour taste, texture, and overall acceptability was liked.